EFEKTIVITAS PEMBELAJARAN BERBASIS PROYEK TERHADAP KREATIVITAS MAHASISWA PGMI - Gusti Handayani (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2018)
The purpose of this study was to determine the effectiveness of the project-based learning model on the creativity of PGMI STIT Al-Hilal Sigli students. The method used in this study was the initial experimental method or pre-experiment with a research design using one-group pretest-posttest. The population in the study were PGMI students in the 2015/2016 academic year, while the sample in this study were 5th semester students. There were two data collection techniques used, which are observation techniques and examination techniques. The instruments used in this study were questionnaires, check scales (rubrics) and questions. The results of the study showed that project-based learning was effective on the creativity of PGMI students.